DIPLOMATIC LANGUAGE EVOLUTION IN THE TEXTS OF INTERNATIONAL AGREEMENTS (based on Karabakh conflict settlement documents) - Shafag F. Ahmedova.; Nazim S. Ibadov. (Вісник університету ім. А. Нобеля. Серія Філологічні науки, 2023)
The purpose of this work is to study diplomatic Russian language evolution, based on the analysis of documents on settlement of the Karabakh conflict and relations between neighboring countries. The objective of the study is to analyze the process of formation of modern vocabulary, features of morphology and syntax in Russian diplomatic language used in negotiation processes and in the preparation of diplomatic documents in the countries of the region in the period from the 18th to the 21st centuries. Since the negotiation processes and documents related to them, based on relations between Russia and the countries of the region, will be considered, cultural-historical, comparative approaches, as well as methods of linguistic observation, contextual, transformational and quantitative analysis are involved in the study. The evolution of the Russian diplomatic language and style is conditioned by both extralinguistic (political situation, wars, changing social formations and the creation of a new state, economic relations, etc.) and linguistic (interaction with other languages, structural and semantic changes, changes in the stylistic affiliation of words) factors influencing the development of the Russian language as a whole. Nevertheless, a number of trends can be identified which characterize the development of the directly diplomatic language: its vocabulary, morphology, and syntax. Changes at these levels reflect the process of the diplomatic language formation as a sphere of official business style and, at the same time, its formation as a unique and self-sufficient diplomatic discourse. The development of the lexical level was largely associated with a change in the composition of the vocabulary used in diplomatic documents in a particular era. The analysis of diplomatic documents shows that in the 18th–19th centuries, the composition of the vocabulary, firstly, indicates that the official business style was at the initial stage of formation; secondly, it reflects the process of the formation of the Russian literary language, a departure from foreign borrowings that actively replenished the language in the era of Peter the Great. This is evidenced by the fact how often are used expressive and evaluative vocabulary, high bookish vocabulary, common and colloquial vocabulary, etiquette-complimentary vocabulary and low frequency of borrowing terms. The desire for maximum accuracy in the presentation of conditions in international treaties is evidenced by the rather high frequency of full and partial synonyms use. Diplomatic vocabulary of the twentieth century (Soviet period) is characterized by the absence of high book vocabulary, a significant increase of common vocabulary, borrowing terms and a decrease of expressive-evaluative, full and partial synonyms and etiquette-complimentary vocabulary. Neologisms, speech (including ideological) clichés come to replace the new formations associated with the construction of the socialist formation state – abbreviations in the texts of notes and internal documents, which indicates the formation of the lexical composition of the official-business style. The composition of the vocabulary of the modern period (the end of the 20th – the first third of the 21st centuries) is characterized by the almost absence in the analyzed documents of expressive-evaluative and etiquette-complimentary vocabulary (which are incorporated into the composition of cliché speech formulas) and is replenished with euphemisms and contextual synonyms. The frequency of use of certain types of vocabulary is changing – a significant increase in speech clichés, a slight increase in neologisms and a decrease in the level of borrowing terms and abbreviations use. Morphologically the analyzed documents texts cut seems to be the most expressive in terms of the impact intentionality degree on the opponent. An indicative trend is the weakening of the semantics of obligation and the strengthening of semantically neutral forms, expressed in the practical rejection of deontic modality use and the infinitive in the function of the imperative mood, as well as in the increasing activity of performative verbs use in the passive voice and verbal nouns. The use of performative verbs in the passive reflects the desire to level the specifics in indicating the persons or organizations in respect of which obligations are determined and allows to neutralize the general tone of the document. The intensive use of verbal names, which form a significant percentage of speech clichés (chancellery), indicates the closest convergence of the diplomatic style with the official business style in the 21st century. In the development of the syntax of diplomatic texts, there is a tendency to simplify constructions, replacing complex sentences with simple ones, including adverbial/participial phrases. The logical presentation, which concludes the subordination of some facts to others, is supported not by a polypredicative construction, but by the topic deployment of content in several monopredicative sentences. Such changes in syntax are due to the desire for brevity, conciseness and maximum accuracy of presentation in conditions of weak individualization of style.